An uncle's guide to GST : the goods & services tax laid bare - Choong, Kwai Fatt , 1965- (Kuala Lumpur, Malaysia : Infoworld, 2014)
An uncle's guide to GST aims to unlock the complexity of the Malaysia's GST model. It explains, with illustrations,the various concepts and mechanism involved, in a simple manner for the easy comprehension of the man in the street.
1. Concept of GST -- 2. Consumer -- 3. Trading -- 4. Manufacturing -- 5. GST administration -- 6. GST audit -- 7. GST appeal
Keywords: Conduct of life; Sales tax -- Malaysia; Taxation -- Malaysia